Viktor Ambartsumian's most important scientific achievements - Mickaelian, A. M.
We give a review of the most important scientific achievements of one of the greatest scientists of the XX century, the founder of the mod- ern astrophysics in Armenia, Viktor A. Ambartsumian (1908-1996). He has fundamentally contributed in various fields of astronomy and astrophysics, cosmogony, theoretical physics, mathematics, and philosophy. We list the most important sscientific results, including his revolutionary works on origin and evolution of stars and activity of galactic nuclei that turned over the development of astrophysics and gave life to our before unchanged Universe. He was one of the founders of the theory of planetary nebulae, stellar dynamics, protostellar dense matter, as well as he has contributed in other important areas of the theoretical astrophysics. Ambartsumian was also a great organizer of science, important political and public figure. He was the founding Director of the Byurakan Astrophysical Observatory (BAO, 1946-1988), the President of the Armenian Academy of Sciences in 1947-1993, the President of the International Astronomical Union (IAU) in 1961-1964 and the President of the International Council of Scientific Unions (ICSU) in 1968-1972. He was the founder of the theoretical astrophysics in the Soviet Union, the founder of chairs of astrophysics in Leningrad (St. Petersburg) and Yerevan state universities, as well as the journals Communications of BAO and Astrofizika (Astrophysics).
Keywords: Astronomy; Famous Armenian astronomers